Implementasi Rekomendasi Diet pada Timbangan Persen Lemak pada Mahasiswa Universitas Muhammadiyah PKU Surakarta: Implementation of Diet Recomendation on Body Fat Scale at the students of Muhammadiyah University PKU Surakarta - Retno Dewi Noviyanti; Ipin Prasojo; Dewi Pertiwi Dyah Kusudaryati; Sri Handayani; Fina Nurrahma; Dilla Sundari Nur Rahmayanti (Amerta Nutrition, 2025)
Background: Accurate nutritional status assessment is essential for designing appropriate dietary recommendations. Conventional body composition analysis tools are often expensive and less accessible. Therefore, the development of modified body fat scales integrated with dietary recommendation features may provide a practical alternative. Objectives: This study aims to implement an integrated dietary recommendation system into body fat scales for students at Muhammadiyah University of PKU Surakarta and to evaluate the measurement accuracy compared to standard devices. Methods: This comparative experimental study involved 60 samples. Measurements included Body Weight (BW), Height (H), Body Mass Index (BMI), body fat percentage, bone density, body fluid, and muscle mass. Data were analyzed using independent sample t-tests and the Mann-Whitney test to compare results between the modified scales and standard (calibrated) scales. Results: The findings indicate no significant differences in body weight, height, and BMI between the modified scales and standard scales (p-value>0.05). However, there were significant differences in body fat percentage (p-value=0.008), bone density (p-value<0.001), body water content (p-value<0.001), and muscle mass (p-value<0.001). Despite these variations, the integrated system successfully provided tailored dietary recommendations based on BMI and body fat analysis. Conclusions: The body fat scale with integrated dietary recommendation features is accurate for assessing basic parameters such as body weight, height, and BMI, while also offering added value through dietary recommendations. Nevertheless, further refinement is necessary to enhance the accuracy of body composition measurements prior to large-scale application.